Thoracoscopic esophagomyotomy. Initial experience with a new approach for the treatment of achalasia. - Pellegrini, C (1992)
The authors treated 17 patients with achalasia by a thoracoscopic (15 patients) or laparoscopic (2 patients) Heller myotomy. All patients had dysphagia and an upper gastrointestinal series demonstrating a dilated esophagus with a bird-beak deformity at the cardia. Manometry showed a mean lower esophageal sphincter (LES) pressure of 32 +/- 4 mmHg, incomplete sphincter relaxation on swallowing, and no primary esophageal peristalsis. After operation, mean LES pressure was 10 +/- 2 mmHg. Fifteen patients were fed on the second postoperative day. The average hospital stay was 3 days, and there were no deaths or major complications. In three early patients, the myotomy was not carried far enough onto the stomach, and dysphagia persisted until a second myotomy was performed (laparoscopically in two patients). The authors found that having an endoscope in the esophagus during the operation facilitated exposure and was vital to determine the appropriate length of the myotomy. With regard to dysphagia, final results were excellent in 12 patients (70%), good in two patients (12%), fair in two patients (12%), and poor in one patient (6%). Heller myotomy can be safely and reliably performed with minimally invasive techniques. Dysphagia is relieved, postoperative pain is minimal, hospital stay is short, and the patient can return quickly to normal activity.